A Longitudinal Examination of CSR Engagement in the Gulf Cooperation Council: An Exploration of Culture and Religion - Alhindi, Huda (Curtin University, 2022)
The present study extends corporate social responsibility (CSR) research in the countries of the Gulf Cooperation Council (GCC) by analysing corporate CSR engagement between 2009 and 2018. Findings confirmed the preservation of cultural traditions and religious beliefs are key drivers of regional corporate CSR interpretation and disclosure practices. Recognition of the influence of culture and religion may result in improvements and increased acceptance and adoption of CSR in the GCC and other Islamic regions.